2007
DOI: 10.1158/0008-5472.can-07-2677
|View full text |Cite
|
Sign up to set email alerts
|

CD83 Gene Polymorphisms Increase Susceptibility to Human Invasive Cervical Cancer

Abstract: We previously mapped a nonrandom frequent loss of heterozygosity (LOH) region in cervical cancers to 1 Mb of 6p23. Here, we describe the identification of a novel cervical cancer susceptibility gene, CD83. The gene was identified by several complementary approaches, including a family-based association study, comparison of transcript expression in normal and cancerous tissue, and genomic sequencing of candidate. CD83 encodes an inducible glycoprotein in the immunoglobulin superfamily and is a marker for mature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 43 publications
2
50
1
Order By: Relevance
“…Therefore, genetic variation of immune system factors may influence susceptibility to cervical cancer (Zur Hausen, 2000;Konac et al, 2007;Jumnainsong, et al, 2007;Schlee et al, 2007;Han et al, 2008;Yu et al, 2009). Recent research has investigated SNPs in CD83, IL-1, IL-6, IL-12, VEGF, and nuclear factor-kappa B in cervical cancer patients (Konac et al, 2007;Zhang et al, 2007;Singh et al, 2008;Castro et al, 2009;Chen et al, 2009;Zhou et al, 2010); however, it remains to be elucidated how the genetic variation is involved in the regulation of the immune response and tumorigenesis (Zhang et al, 2007;Yu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, genetic variation of immune system factors may influence susceptibility to cervical cancer (Zur Hausen, 2000;Konac et al, 2007;Jumnainsong, et al, 2007;Schlee et al, 2007;Han et al, 2008;Yu et al, 2009). Recent research has investigated SNPs in CD83, IL-1, IL-6, IL-12, VEGF, and nuclear factor-kappa B in cervical cancer patients (Konac et al, 2007;Zhang et al, 2007;Singh et al, 2008;Castro et al, 2009;Chen et al, 2009;Zhou et al, 2010); however, it remains to be elucidated how the genetic variation is involved in the regulation of the immune response and tumorigenesis (Zhang et al, 2007;Yu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Also, genetic factors involved in immune recognition and antigen presentation may play a crucial role in the pathogenesis of cervical cancer (Zur Hausen, 2000;Han et al, 2008). Zhang et al (2007) reported an association between cervical cancer and five single-nucleotide polymorphisms (SNPs) of CD83. Yu et al (2009) replicated this study and confirmed the possible role of CD83 polymorphisms in cervical carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Normal cervix and cervical cancer tissues were obtained from women with an age range from 40 to 50 yr old. HPV genotyping was done by sequencing-based techniques as previously described (Zhang et al 2007). Use of these tissues was approved both by the Washington University Medical Center Human Studies Committee and by the NIH Office of Human Subjects Research.…”
Section: Cell Lines and Human Tissuesmentioning
confidence: 99%
“…HPV infection in the anogenital tract is a common sexually transmitted disease that usually produces transient cervical inflammation; neoplasia is in fact very uncommon [24]. Differences in the response to HPV infection may be linked to immune status, such as the presence of HIV infection, or to genetic factors,such as HLA type [25], CD83 polymorphisms, [26] or single-nucleotide polymorphisms (SNPs) at the IL-10 promoter or the Fas promoter [25,27]. Nevertheless, HPV is considered the single most important factor in the development of cervical carcinoma, and HPV DNA would undoubtedly be identified in almost all specimens of invasive cervical carcinoma if the appropriate molecular technology were used [23,28].…”
Section: Discussionmentioning
confidence: 99%